2013
DOI: 10.4103/0974-1208.126285
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone and follicle stimulating hormone synergy: A review of role in controlled ovarian hyper-stimulation

Abstract: Luteinizing hormone (LH) in synergy with follicle stimulating hormone (FSH) stimulates normal follicular growth and ovulation. FSH is frequently used in assisted reproductive technology (ART). Recent studies have facilitated better understanding on the complementary role of the LH to FSH in regulation of the follicle; however, role of LH in stimulation of follicle, optimal dosage of LH in stimulation and its importance in advanced aged patients has been a topic of discussion among medical fraternity. Though th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 58 publications
(75 reference statements)
1
53
0
1
Order By: Relevance
“…Estrogen promotes granulosa cell growth and increases the number of FSH and luteinizing hormone (LH) receptors. FSH in turn regulates estrogen production by p450 aromatase, and LH synergizes with FSH to promote follicular growth and ovulation to maintain a normal rate of growing follicles [14]. Later stages of follicle development are regulated by activins and estradiol, further increasing the number of FSH receptors.…”
Section: Establishment and Overall Dynamics Of The Ovarian Reservementioning
confidence: 99%
“…Estrogen promotes granulosa cell growth and increases the number of FSH and luteinizing hormone (LH) receptors. FSH in turn regulates estrogen production by p450 aromatase, and LH synergizes with FSH to promote follicular growth and ovulation to maintain a normal rate of growing follicles [14]. Later stages of follicle development are regulated by activins and estradiol, further increasing the number of FSH receptors.…”
Section: Establishment and Overall Dynamics Of The Ovarian Reservementioning
confidence: 99%
“…At birth, the mammalian ovary contains numerous of primordial follicles, and these begin to undergo folliculogenesis during puberty and will eventually be ovulated or will degrade in a process known as atresia. The decision as to whether a follicle will develop or ovulate or undergo atresia is regulated by a variety of factors 2 3 4 .…”
mentioning
confidence: 99%
“…Thus, LH association to FSH during follicular development may promote a more physiologically environment, and can be a manner to improve oocyte maturation. Some authors observed that the presence of LH activity may have a positive effect on oocyte maturation (Selman et al, 2002;Pacchiarotti et al, 2007;Santi et al, 2017) and LH supplementation had been correlated to higher number of mature oocytes in COS protocols for anovulatory patients (Burgués & Spanish Collaborative Group on Female Hypogonadotrophic, 2001; Raju et al, 2013) or patients with poor ovarian response (Papaleo et al, 2014).…”
Section: Clinical Outcomesmentioning
confidence: 99%